A multi-nation examination of the fatigue and recovery time course during the inaugural Under-18 Six Nations rugby union competition. Issue 6 (18th March 2020) - Ramírez-López, Carlos; Till, Kevin; Sawczuk, Thomas; Giuliano, Pierosario; Peeters, Alexis; Beasley, Grant; Murray, Fraser; Pledger, Stephen; Read, Dale; Jones, Ben
ABSTRACT: The purpose of this study was to investigate the neuromuscular and perceptual fatigue responses of elite rugby players during the inaugural Under-18 (U18) Six Nations Festival. One hundred and thirty-three male players from five national squads (73 forwards, 60 backs) were examined during the competition. Each national squad was involved in three matches separated by 96 h each. Over the competition, players completed a daily questionnaire to monitor perceived well-being (WB) and performed daily countermovement jumps (CMJ) to assess neuromuscular function (NMF). Reductions in WB were substantial 24 h after the first and second match in forwards ( d =0.77±0.21, p<0.0001; d =0.84±0.22, p< 0.001) and backs ( d =0.89±0.22, p <0.0001; d =0.58±0.23, p<0.0001) but reached complete recovery in time for the subsequent match. Reductions in CMJ height were substantial 24 h after the first and second match for forwards ( d =0.31±0.15, p=0.001; d =0.25±0.17, p=0.0205) and backs ( d =0.40±0.17, p=0.0001; d =0.28±0.17, p=0.0062) and recovered at 48 h after match-play. Average WB and CMJ height attained complete recovery within matchday cycles in the investigated international competition. The findings of this study can be useful for practitioners and governing bodies involved with fixture scheduling and training prescription during competitive periods.